Reversal of Graft-Versus-Host Disease with Infusion of Autologous Bone Marrow - Camillo Ricordi M.D. (Cell Transplantation, 1994)
Graft-versus-host disease (GVHD) remains a major complication of bone marrow transplantation. This report describes reversal of GVHD by infusion of stored recipient bone marrow following combined liver-bone marrow allotransplantation. Graft-versus-host disease developed at the end of the first postoperative week. The skin involvement progressively spread to approximately 80% of the body surface and was not affected by modification of the immunosuppressive treatment. On the 42nd and 43rd postoperative day 1.23 × 108 and 1.6 × 108 autologous bone marrow cells per kg of recipient body weight were infused. The skin rush began to dramatically improve and resolved within 2 wk from the autologous marrow infusion. Autologous bone marrow storage previous to allogeneic bone marrow transplantation for tolerance induction could constitute a safety net in case of occurrence of GVHD.